Local Candidates and Distributive Politics under Closed-list Proportional Representation - Jon H. Fiva; Askill Halse; Daniel M. Smith (Center for Economic Studies and ifo Institute (CESifo), 2018)
Geographic representation is an important consideration in candidate nominations, even under closed-list proportional representation (PR), and may even matter for distributive policy outcomes. However, since nominations are determined strategically, the causal effects of local representation are difficult to identify. We investigate the relationship between local representation and electoral and distributive politics in the closed-list PR setting of Norway. Exploiting as-good-as-random election outcomes for marginal candidates, we find that parties obtain higher support in subsequent elections in the hometowns of narrowly-elected candidates. This effect appears to be driven by the local candidate appearing at the top of the party list in the next election. However, we find no evidence that representation results in geographically targeted policy benefits going to the candidates' hometowns.
Keywords: D72; 330; distributive politics; representation; voting behavior